Varying Power Configurations and the Accountability of Independent Regulatory Agencies - Fulya Apaydin; Jacint Jordana (International Review of Public Policy)
Independent regulatory agencies (IRAs) have a significant capability to choose how to implement their decisions to be effective, given the mix of managerial autonomy, supervisory powers and political independence that most of these agencies enjoy. As such, traditional approaches which focus on their institutional characteristics or their reputational problems do not fully capture the variation in IRAs’ behavior. This paper suggests a complementary approach to interpreting IRAs’ autonomous behavior, focusing on the possibilities that the practice of accountability offers to these public agencies to make relevant choices for the agency itself and the policy environment. To that end, we identify a key background variable that affects the practice of IRAs, namely, the varying power configurations existing among the regulatees and focus on how this factor shapes their voluntary accountability in different contexts. Lastly, we examine several cases of IRA accountability behavior to discuss whether the patterns we submit might constitute a starting point for a theoretical development on the use of accountability by IRAs.